GPU-accelerated two dimensional synthetic aperture focusing for photoacoustic microscopy - Liu, Siyu (2019)
Acoustic resolution photoacoustic microscopy (AR-PAM) generally suffers from limited depth of focus, which had been extended by synthetic aperture focusing techniques (SAFTs). However, for three dimensional AR-PAM, current one dimensional (1D) SAFT and its improved version like cross-shaped SAFT do not provide isotropic resolution in the lateral direction. The full potential of the SAFT remains to be tapped. To this end, two dimensional (2D) SAFT with fast computing architecture is proposed in this work. Explained by geometric modeling and Fourier acoustics theories, 2D-SAFT provide the narrowest post-focusing capability, thus to achieve best lateral resolution. Compared with previous 1D-SAFT techniques, the proposed 2D-SAFT improved the lateral resolution by at least 1.7 times and the signal-to-noise ratio (SNR) by about 10 dB in both simulation and experiments. Moreover, the improved 2D-SAFT algorithm is accelerated by a graphical processing unit that reduces the long period of reconstruction to only a few seconds. The proposed 2D-SAFT is demonstrated to outperform previous reported 1D SAFT in the aspects of improving the depth of focus, imaging resolution, and SNR with fast computational efficiency. This work facilitates future studies on in vivo deeper and high-resolution photoacoustic microscopy beyond several centimeters.